God's body the anthropomorphic God in the old testament - Wagner, Andreas 1963-; Salzmann, Marion (London New York Oxford New Delhi Sydney T&T Clark, 2019)
An investigation into the external body of God as it can be portrayed pictorially -- The picture of God, Yhwh in the corporeal form of man -- God in human form, anthropomorphism as a theological problem -- Deciphering the language of images and of corporeal depictions -- God's body (the external figure), its theological message -- The picture of God in the Old Testament and of mankind made in the image of God
Keywords: Bible -- Criticism, interpretation, etc; Image of God -- Biblical teaching; God -- Corporeality; Bible ; Old Testament; God ; Corporeality; Image of God ; Biblical teaching; Criticism, interpretation, etc